CIRENG AND CIMOL NELLA BUSINESS INNOVATIONS: NEW PRODUCT DEVELOPMENT & FINANCIAL ASPECT METHOD IN THE NEW NORMAL ERA - Sulaksana, Fia Dialysa; Prasetyo, Mohamad Hadi (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2023)
Cireng and Cimol NELLA are one of the many business people affected by the COVID-19 outbreak. The pandemic situation makes this business have to innovate, consumers must feel the added value and new experiences in consuming it. The problems that arise are the absence of product development, as well as the limited capital equipment used to increase production capacity, so that the profits received are not maximized. Method (1) on the marketing side is carried out from idea generation, idea screening, concept development, marketing strategy, business analysis, product development, test marketing, and commercialization. (2) the financial side, namely calculating the Break Even Point, Net Present Value, Payback Period, Internal Rate of Return, B/C Ratio. The results of this service are: (1) adding product variations: salt chili flavored cireng, melted cheese cireng, and salt chili cheese cireng (2) selected marketing strategy: buy 2 get 1 free, bundling package. (3) conduct product development analysis, test marketing with the chosen strategy, and conduct commercialization on the marketplace. (4) in terms of financial calculations, this business is feasible to be developed and profitable for the culinary industry in the future.